Analysis of Water Sign Needs on the Rowosari River, Kendal Regency, Central Java Province - Triwahyuni, Siti Nurliali; Arkani, Hari; Puspitasari, Novrianti; Panggabean, Yunita; Maulana, Restu Agung (IWJ : Inland Waterways Journal, 2025)
The Rowosari River in Kendal Regency plays a strategic role as a water transportation route connecting regions and supporting the community's socio-economic activities. Observations indicate that the signage facilities on the Kendal-Batang route are still suboptimal because there is only one prohibition sign installed, potentially reducing navigation safety and effectiveness. This study aims to analyze the need for water signs on the Rowosari River based on existing conditions, river morphological characteristics, hydrographic factors, and applicable technical provisions. The method used is descriptive qualitative through field observation, visual documentation, GPS coordinates, and literature and institutional data studies. The analysis results indicate the need for the addition of 32 signs consisting of 21 guide signs, 7 prohibition signs, 2 command signs, and 2 warning signs. The distribution of signs is designed to be placed at strategic points such as sharp bends, channel intersections, and anchorage areas, with technical specifications in accordance with the Regulation of the Director General of Land Transportation No. KP.4755/AP005/DRJD/2020. These recommendations are expected to improve shipping safety, navigation effectiveness, and the smoothness of water transportation in the region.